Rancangan Aplikasi Pencarian Lokasi Tempat Ibadah Di Kota Bengkulu Menggunakan Location Based Service Berbasis Android - Icuk Gempa Ulit; Agung Kharisma Hidayah; Muntahanah Muntahanah; Dedy Abdullah (UNIVED Press, 2024)
Bengkulu City has many destinations that can attract visitors to visit Bengkulu City. The migrant community consists of various ethnicities and religions and there are also foreign tourists. Most visitors who come to Bengkulu City for the first time find it difficult to find the location of a place of worship. Most immigrants use Android-based cellphones in their daily lives. So researchers took the initiative to create an application to search for places of worship by utilizing the location based service (LBS) system. LBS is a system for finding the coordinates of a device's location. Therefore, by using the location based service method to create an Android-based application for finding the location of places of worship and finding out information on the state of places of worship in Bengkulu City. This research ends in design form and it is hoped that future researchers will implement the research results, namely creating a search application for places of worship using an Android-based location based service